2023
DOI: 10.1186/s12967-023-04456-1
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Metformin for periodontal disease management as a form of oral-systemic preventive medicine

Vitor C. M. Neves,
Luciana Satie Okajima,
Eyad Elbahtety
et al.

Abstract: Background Despite the improvements in treatment over the last decades, periodontal disease (PD) affects millions of people around the world and the only treatment available is based on controlling microbial load. Diabetes is known to increase the risk of PD establishment and progression, and recently, glucose metabolism modulation by pharmaceutical or dietarian means has been emphasised as a significant modulator of non-communicable disease development. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In order to investigate its potential in alleviating periodontitis progression by targeting aging, we analyzed single cell RNA sequencing data of GSE242714 from gingiva tissue of periodontitis mice treated with metformin. The results indicated that metformin could reduce the aging characteristics of the overall gingiva (Neves et al, 2023) (Supplementary Fig. 1A).…”
Section: Introductionmentioning
confidence: 95%
“…In order to investigate its potential in alleviating periodontitis progression by targeting aging, we analyzed single cell RNA sequencing data of GSE242714 from gingiva tissue of periodontitis mice treated with metformin. The results indicated that metformin could reduce the aging characteristics of the overall gingiva (Neves et al, 2023) (Supplementary Fig. 1A).…”
Section: Introductionmentioning
confidence: 95%